Evaluation of Vocational Training Programs with CIPP Evaluation Model and CSE-UCLA Evaluation Model - Salsabilla, Imelia Sahda; Bakhri, Syaiful; Asiyah, Nur (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to evaluate the vocational training program at the Semarang Vocational Training and Productivity Center (BBPVP) using 2 evaluation models, namely CIPP (Context, Input, Process, Product) and CSE-UCLA (Planning, Development, Implementation, Improvement, Certification). The background of this research departs from the phenomenon of competency gap due to digital disruption, automation, and green transition that requires the vocational world to be more adaptive to the needs of the global industry. In Islamic education management, this evaluation is understood as a form of effort to improve the quality of human resources in accordance with the principle of self-change as stated in QS. Ar-Ra'd: 11. This study uses an evaluative qualitative approach with observation, in-depth interviews, and documentation. The data analysis technique uses the Miles and Huberman interactive analysis model, which includes three main stages, namely data reduction, data presentation, and conclusion/verification. The results of the study show that the training program is effective in improving the technical skills and soft skills of participants, especially in the fields of office administration, Administrative Assistant, Digital Marketing. However, several obstacles were found such as the limitations of print teaching modules, the variety of instructors, and the need to improve vocational terms or business terms. Overall, both the CIPP and CSE-UCLA models have been shown to provide a holistic picture of the effectiveness, relevance, and sustainability of the program. This study concludes that BBPVP Semarang has successfully carried out vocational training that is relevant to the needs of the industry, but needs to be improved in terms of curriculum, facilities, and digitalization. The researcher recommends that institutions continue to update the curriculum based on industry needs, expand cooperation with the industrial world, and implement a practice-based learning approach and soft skills to strengthen the competitiveness of the vocational workforce in the era of digital transformation. Keywords: Vocational Training Program Evaluation, CSE-UCLA evaluation model, CIPP evaluation model